Mapping the pollutants in surface riverine flood plume waters in the Great Barrier Reef, Australia - Devlin, M.; McKinna, Lachlan; Álvarez-Romero, J.; Petus, C.; Abott, B.; Harkness, P.; Brodie, J. (Pergamon, 2012)
The extent of flood plume water over a 10 year period was mapped using quasi-true colour imagery and used to calculate long-term frequency of occurrence of the plumes. The proportional contribution of riverine loads of dissolved inorganic nitrogen, total suspended sediments and Photosystem-II herbicides from each catchment was used to scale the surface exposure maps for each pollutant. A classification procedure was also applied to satellite imagery (only Wet Tropics region) during 11 flood events (2000– 2010) through processing of level-2 ocean colour products to discriminate the changing characteristics across three water types: ‘‘primary plume water’’, characterised by high TSS values; ‘‘secondary plume water’’, characterised by high phytoplankton production as measured by elevated chlorophyll-a (chl-a), and ‘‘tertiary plume water’’, characterised by elevated coloured dissolved and detrital matter (CDOM + D). This classification is a first step to characterise flood plumes.